Seismic Shot Point Navigation Data from the Tjornes Fracture Zone, offshore Northern Iceland, acquired during the R/V Bjarni Saemundsson expedition BSTFZB9 (2001) (IEDA: Marine-Geo Digital Library, 2009)
This data set was acquired with the LDEO Portable HiRes Multi-Channel Seismic system during R/V Bjarni Saemundsson expedition BSTFZB9 conducted in 2001 (Chief Scientist: Dr. Robert Detrick; Investigators: Dr. Robert Detrick, Dr. Neal Driscoll, and Dr. Bryndis Brandsdottir). These data files are of ASCII format and include Seismic Shot Point Navigation data that provide the primary seismic navigation source for this cruise. Data were acquired as part of the project: Pilot Study of the Tjornes Fracture Zone, offshore Northern Iceland, using High-Resolution Multi-channel Seismic Reflection Profiling and CHIRP Sonar, and funding was provided by NSF grant: OCE01-14357.